2018
DOI: 10.1111/joes.12269
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Active Labor Market Policies: A Meta‐analysis

Abstract: Abstract. This paper provides a meta-analysis of microeconometric evaluation studies on the effectiveness of active labor market policies. The analysis is built upon a systematically assembled data set of causal impact estimates from 57 experimental and quasi-experimental studies, providing 654 estimates published between January 1990 and December 2017. We distinguish between the short and longer term impacts in our analysis; at 6, 12, 24, and 36 months after program start. After correcting for publication bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 98 publications
4
69
0
4
Order By: Relevance
“…We were unable to examine this as most studies did not report intervention intensity or duration, although the single most intense intervention did yield the largest effect. Another explanation is a lock-in effect (Card et al, 2010;Vooren et al, 2019). Participants reduce their entrepreneurial activity during an intervention, which may have negative short-term effects on entrepreneurial performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were unable to examine this as most studies did not report intervention intensity or duration, although the single most intense intervention did yield the largest effect. Another explanation is a lock-in effect (Card et al, 2010;Vooren et al, 2019). Participants reduce their entrepreneurial activity during an intervention, which may have negative short-term effects on entrepreneurial performance.…”
Section: Discussionmentioning
confidence: 99%
“…Since they are not comparable across studies, we convert them into a second set of standardized estimates. The conversion is initially conducted using Cohen's d estimator (1969), which is widely used in psychology and education studies and more recently also in economics (e.g., Cho and Honorati, 2014;Vooren et al, 2019). Cohen's d gives the mean difference in entrepreneurial performance between treatment and control groups, expressed in (pooled) standard deviations rather than raw scores.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Martin (2015, p. 29) finds that ALMPs are generally effective at finding jobs for the unemployed, but many countries only 'pay lip service' to labour activation in order to artificially manipulate the unemployment numbers and institute welfare-to-work schemes. In a recent study, Vooren et al (2018) have shown that ALMPs in general have negative impacts over the short term, with a longer-term net benefit for society and the participant. But ALMPs that have considerable training elements will avoid this initial negative impact (Vooren et al, 2018, p. 15).…”
Section: The Design Flaws In Jobbridgementioning
confidence: 99%
“…In Slovakia, it is primarily about financing activation work. Several authors note that the activation work is the least effective [13]. In 2016, Sweden wanted to focus on the investment related to the overcoming of the long-term unemployment, the people with disabilities that have a decreased ability to work, faster deployment of newcomers, a better income in the whole country, support of the employment of young people, modern working life [10], [11].…”
Section: Structure Of Expenditures On the Active Labor Market Polmentioning
confidence: 99%